The ecology and tree species of urban green areas within the municipality of Campestre, Minas Gerais - Sobral, Lilian Martins; Marcelini, Diego Pereira; Reis, Miguel Gama; Ferreira-Júnior, Walnir Gomes (Revista Agrogeoambiental, 2021)
Urban green areas produce benefits such as reduced air pollution, climate mitigation, reduced wind action, less noise pollution, shelter for fauna, and increased water uptake from the soil as well as increased water infiltration to the soil. This work carried out a floristic survey related to its diverse and characterized habit and dispersion, and also related to the origin of the species existing in four public squares within the municipality of Campestre, Minas Gerais. Thus, the floristic and ecological aspects of trees and shrubs were surveyed in four urban green areas of the municipality. All arboreal and shrubby individuals were marked and identified. Each identified species was classified according to habit, dispersion, and origin. In total, 313 tree individuals, shrubs, and palm trees were registered and distributed among 73 species, (62 genera and 30 botanical families). When considering all squares, Shannon’s diversity was 3.72, and Pielou’s evenness coefficient was 0.87. Lower values of diversity and evenness were observed for each public square. There was greater richness and number of individuals of native species compared to exotic ones. The yellow ipe (Handroanthus serratifolius) was the only species present in all studied squares. Sassafras (Ocotea odorifera) and pau-brasil (Paubrasilia echinata) are endangered species and underrepresented. The most represented forms of dispersion were zoochory and anemochory.